Selective internal radiation therapy for liver malignancies. Issue 12 (14th September 2015) - Moir, J. A. G.; Burns, J.; Barnes, J.; Colgan, F.; White, S. A.; Littler, P.; Manas, D. M.; French, J. J.
<x xml:space="preserve">Abstract</x> Background Selective internal radiation therapy (SIRT) is a non‐ablative technique for the treatment of liver primaries and metastases, with the intention of reducing tumour bulk. This study aimed to determine optimal patient selection, and elucidate its role as a downsizing modality. Methods Data were collected retrospectively on patients who underwent SIRT between 2011 and 2014. The procedure was performed percutaneously by an expert radiologist. Response was analysed in two categories, based on radiological (CT/MRI according to Response Evaluation Criteria In Solid Tumours (RECIST)) and biological (α‐fetoprotein, carcinoembryonic antigen, carbohydrate antigen 19‐9, chromogranin A) parameters. Results Forty‐four patients were included. Liver metastases from colorectal cancer (22 patients) and hepatocellular carcinoma (HCC) (9) were the most common pathologies. Radiological response data were collected from 31 patients. A reduction in sum of diameters (SOD) was observed in patients with HCC (median −24·1 (95 per cent c.i. –43·4 to −3·8) per cent) and neuroendocrine tumours (−30·0 (−45·6 to −7·7) per cent), whereas a slight increase in SOD was seen in patients with colorectal cancer (4·9 (−10·6 to 55·3) per cent). Biological response was assessed in 17 patients, with a reduction in 12, a mixed response in two and no improvement in three. Six‐ and 12‐month overall survival rates were 71 and 41 per cent respectively. There was no difference in overall survival between the RECIST response groups (median survival 375, 290 and 214 days for patients with a partial response, stable disease and progressive disease respectively; P = 0·130), or according to primary pathology (P = 0·063). Seven patients underwent liver resection with variable responses after SIRT. Conclusion SIRT may be used to downsize tumours and may be used as a bridge to surgery in patients with tumours deemed borderline for resection.